2022
DOI: 10.1111/ijpo.12887
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics reveals sex‐specific pathways associated with changes in adiposity and muscle mass in a cohort of Mexican adolescents

Abstract: Summary Background Alterations in body composition (BC) during adolescence relates to future metabolic risk, yet underlying mechanisms remain unclear. Objectives To assess the association between the metabolome with changes in adiposity (body mass index [BMI], waist circumference [WC], triceps skinfold [TS], fat percentage [BF%]) and muscle mass (MM). Methods In Mexican adolescents (n = 352), untargeted serum metabolomics was profiled at baseline. and data were reduced by pairing hierarchical clustering with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…However, the aforementioned relationships may have differences when analyzed by sex. Given that, in terms of body composition, there are differences in the proportion of fat mass and muscle mass between the sexes [19], it is expected that there will be differences in exercise performance, which may be accentuated by gender aspects and traditional roles. It has been observed that more men engage in physical exercise than women, and men also dedicate more time to the practice than women [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the aforementioned relationships may have differences when analyzed by sex. Given that, in terms of body composition, there are differences in the proportion of fat mass and muscle mass between the sexes [19], it is expected that there will be differences in exercise performance, which may be accentuated by gender aspects and traditional roles. It has been observed that more men engage in physical exercise than women, and men also dedicate more time to the practice than women [20].…”
Section: Introductionmentioning
confidence: 99%
“…Ornithine is involved in the urea cycle, and its increase could indicate a rise in the urea cycle to eliminate ammonia produced by amino acid degradation during chronic training [51]. In males, but not in females, branched chain amino acids have been associated with an increase in body mass, as reported by Rodriguez-Carmona et al [52], and in our experimental conditions, we found a significant increase in L-valine and L-threonine in the saliva of male athletes only. As expected, in male athletes, a training-related metabolic pathway is associated with valine, leucine, and isoleucine biosynthesis, considering that branched chain amino acids are associated with an increase in skeletal muscle mass, which is related to sex-specific differences in whole body muscle mass [53][54][55].…”
Section: Discussionmentioning
confidence: 76%
“…We also demonstrate batchCombine on metabolomics data from ELEMENT, a wellcharacterized birth-cohort study that collected fasting serum from 402 Mexico City adolescents [13,19]. Samples were partitioned into eight batches, each composed of roughly fifty subject samples and nine pooled QCs.…”
Section: Alignment Of the Multi-batch Element Study With Batchcombinementioning
confidence: 99%
“…The Early Life Exposure in Mexico to Environmental Toxicants (ELEMENT) study was founded in the early 1990s as previously described [13]. The blood samples of 402 adolescent volunteers from the ELEMENT 2015 study visit were analyzed with an untargeted metabolomics assay at the Michigan Regional Comprehensive Metabolomics Resource Core (MRC 2 ) [19]. Serum samples were thawed on ice prior to processing.…”
Section: Early Life Exposures In Mexico To Eevironmental Toxicants (E...mentioning
confidence: 99%